Low dose naloxone for pruritus in systemic sclerosis: Case series and literature review. Issue 4 (28th January 2022) - Meridor, Katya; Berookhim, Joshua; Levy, Yair
Abstract: Rationale: Pruritus is a common symptom in patients with systemic sclerosis and has a tremendous effect on the quality of life. Nevertheless, current therapeutic options are limited. The pathogenesis of pruritus in systemic sclerosis is not completely understood; however, opiate-mediated neurotransmission has been postulated to be involved. Patient concerns and diagnosis: We describe 4 female patients with systemic sclerosis suffering from severe pruritus, with an average 5D-itch score of 22.75. Intervention and outcomes: Low-dose oral naloxone was initiated, followed by a significant improvement in the level of pruritus, reaching an average 5D-itch score of 7.5, after 6 and 12 months of treatment. None of the patients experienced side effects. Lessons: Low-dose naloxone plays an important role in the management of pruritus in systemic sclerosis.